Globalization and social determinants of health: The role of the global marketplace (part 2 of 3) - Schrecker Ted; Labonté Ronald (BMC, 2007)
Abstract Globalization is a key context for the study of social determinants of health (SDH): broadly stated, SDH are the conditions in which people live and work, and that affect their opportunities to lead healthy lives. In the first article in this three part series, we described the origins of the series in work conducted for the Globalization Knowledge Network of the World Health Organization's Commission on Social Determinants of Health and in the Commission's specific concern with health equity. We identified and defended a definition of globalization that gives primacy to the drivers and effects of transnational economic integration, and addressed a number of important conceptual and methodological issues in studying globalization's effects on SDH and their distribution, emphasizing the need for transdisciplinary approaches that reflect the complexity of the topic. In this second article, we identify and describe several, often interacting clusters of pathways leading from globalization to changes in SDH that are relevant to health equity. These involve: trade liberalization; the global reorganization of production and labour markets; debt crises and economic restructuring; financial liberalization; urban settings; influences that operate by way of the physical environment; and health systems changed by the global marketplace.